Dietary guidelines for water and electrolytes - What role for thirst? - Schnirring, L. (The Physician and Sportsmedicine, 2004)
The traditional water intake recommendation of eight glasses a day never had a formal scientific basis or backing. To establish an evidence-based recommendation for water intake, an expert panel of US and Canadian scientists recently examined the issue, along with electrolyte intake, on behalf of the Institute of Medicine (IOM), and published their findings in February.1 The IOM is a division of the National Academy of Sciences, an independent, nonprofit organization that advises government agencies on scientific and technological matters. Advice is given especially for athletes.